Implementasi Karakter Kreatif Organisasi Ikatan Jamaah Majelis Ta'lim Untuk Memakmurkan Masjid - Hanis Asmar Hanis; Yogi Nugraha; Erwin Susanto (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2021)
The research aims to investigate the implementation of creative character the of Al-Barkah Majlis Ta’lim Jama’ah Association to prosper the mosque. This research is a qualitative research with a descriptive method. The techniques of research used are conducted direct observations and interviews with the head, the deputy head, and the three members of Al-Barkah Majlis Ta’lim Jama’ah Association. The data collection techniques used in this research are direct observations and interviews with the subjects of the research. The result of the research showed that implementing creative character could bring a change to the organization. It brought prosperity to the mosque. This research is based on the fact that Al-Barkah Majlis Ta’lim Jama’ah Association could make a change by rebuilding the prosperity of the mosque that had not been used for Islamic activities in a while. Now the mosque is starting to be packed with Islamic activities again. From the conducted research, several activities are done by of Al-Barkah Majlis Ta’lim Jama’ah Association in implementing creative character. Therefore, it can be concluded that the implementation of creative character in the activities of Al-Barkah Majlis Ta’lim Jama’ah Association contributes to prosper the mosque.